Improvements in the thermomechanical and electrical behavior of hybrid carbon-epoxy nanocomposites - López-Barroso, Juventino; Garcia Casillas, Perla Elvia; Martínez-Hernández, Äna Laura; Rivera-Armenta, Jose Luis; Almendarez-Camarillo, A; Flores-Hernández, CG; Velasco-Santos, Carlos (2021)
In this work, polymeric composites of epoxy matrix reinforced with 1D and 2D nanocarbon allotropes are reported. Hybrid 3D nanostructures formed from 1D multi-walled carbon nanotubes and 2D graphene derivatives improve the electrical and thermomechanical response of the synthesized nanocomposites. Additionally, oxygenated moieties in the surface of the sp2 carbon allotropes positively influences the dispersion of nanomaterials in the matrix and promote better interfaces among the polymeric matrix and reinforcements. Raman spectroscopy detects the different interactions of polymeric chains with carbon nanomaterials in different loads. Furthermore, Raman mapping shows the carbon dispersion regions and the influence on the final mechanical properties of the materials. The viscoelastic response evaluated by Dynamical Mechanical Analysis shows improvements of up to 138% in the storage modulus of nanocomposites with oxidized nanostructures in comparison to neat epoxy. 3D nanostructures changed the insulating nature of epoxy when the carbon nanomaterials formed the interconnected network. Some nanocomposites show an abrupt change from the insulator epoxy resin toward a semiconductor response, mainly in hybrids reinforced with pristine multi-walled carbon nanotubes and reduced graphene oxide. The TEM images of the nanocomposites showed interconnections between the 1D-2D hybrid carbon nanomaterials, which suggest a synergetic effect